Optic nerve involvement in CACNA1F-related disease: observations from a multicentric case series. (4th March 2023) - Marziali, Elisa; Van Den Broeck, Filip; Bargiacchi, Sara; Fortunato, Pina; Caputo, Roberto; Sodi, Andrea; De Zaeytijd, Julie; Murro, Vittoria; Mucciolo, Dario Pasquale; Giorgio, Dario; Passerini, Ilaria; Palazzo, Viviana; et al.
ABSTRACT: Background: Congenital Stationary Night Blindness (CSNB) constitutes a group of non-progressive retinal disorders characterized by disturbances in scotopic vision and/or by a delay in adaptation to darkness, as well as by low visual acuity, myopia, nystagmus, and strabismus. Color vision and fundus appearance tend to be normal. To date, several CACNA1F gene variants have been linked to a CSNB phenotype but only few reports have focused on the optic nerve in this disease. Materials and Methods: Twelve patients underwent standard ophthalmological and genetic evaluation including spectral domain optical coherence tomography (SD-OCT), full-field electroretinography (ffERG), kinetic perimetry, fundus photography, magnetic resonance imaging (MRI), and next-generation sequencing (NGS). Bilateral thinning of the peripapillary nerve fiber layer (pRNFL) and the ganglion cell complex (GCC) supported involvement of the optic nerves. MRI, when available, was assessed for gross intracranial optic pathway abnormalities. Results: All patients were shown to carry pathogenic variants in the CACNA1F gene, and all showed signs of optic nerve involvement. All patients showed a certain degree of myopic refractive error. Low average pRNFL thickness was evident in all patients. In three of them, pRNFL thickness was evaluated longitudinally and was proven to be stable over time. MRI imaging was unremarkable in all cases. Conclusion: Our data support the hypothesis that CACNA1F could be related to early-onset or congenital optic nerve involvement without any signs of a progressive optic neuropathy. Even though additional data from larger cohorts and longer follow-up periods are needed to further support and confirm our findings, there is a clear significance to our findings in the preparation for future CACNA1F gene therapy trials.